Pharmacokinetics and tolerability of single-dose enteral cannabidiol and cannabidiolic acid rich hemp in horses (Equus caballus) - Thomson, Alexander C. S.; McCarrel, Taralyn M.; Zakharov, Alexander; Gomez, Beatriz; Lyubimov, Alex; Schwark, Wayne S.; Mallicote, Martha F.; Portela, Diego A.; Bisiau, Amber L.; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2024)
The pharmacokinetics and tolerability of cannabinoids and their metabolites were determined in eight horses after enteral administration of a commercial CBD/CBDA-rich hemp oil product. Each horse was administered 2 mg/kg or 8 mg/kg CBD/CBDA or no treatment in a randomized cross-over design. Serial serum samples collected over 48 h were analyzed by high performance liquid chromatography with tandem mass spectrometry. Plasma chemistry analysis was performed at 0 h and 24 h. Vital parameters, pedometry, and blinded mentation and gait evaluations were recorded at intervals up to 24 h. Manure production and gastrointestinal transit time were tracked for 48 h after oil administration. The median maximal concentration of CBD and CBDA were 5.2 and 36.95 ng/mL in the 2 mg/kg group, respectively; and 40.35 and 353.56 ng/mL in the 8 mg/kg group. The median half-life of elimination was not calculated for the 2 mg/kg CBD treatment due to lack of time points above the lower quantifiable limit beyond the Cmax while it was 7.75 h in the 8 mg/kg group. CBDA absorption was biphasic. Pharmacokinetic parameters for tetrahydrocannabinol, tetrahydrocannabinolic acid, cannabigerolic acid, and 7-carboxy cannabidiol are also reported. No significant differences in any of the measured tolerability parameters were demonstrated between treatment groups. Single-dose enteral administration of CBD/CBDA-rich hemp extract up to 8 mg/kg does not appear to produce neurologic, behavioral, or gastrointestinal effects in horses.